Open grazing and cropping intensity in the Brahmaputra Valley - Jayanta Saud; M P Bezbaruah (Agricultural Economics Research Review, 2023)
After farmers in the Brahmaputra Valley harvest winter rice, they let their cattle graze in the village fields. Open grazing surfaces often in discussions on the problems of agriculture in Assam, but it has not been studied yet. This paper investigates the phenomenon, and it finds that open grazing significantly limits cropping intensity. If farmer communities collaborate with extension agencies, they may be able to protect the seasonal commons nature of the fields and also grow a second crop.